Ряди Фур’є періодичних функцій зі змінним періодом - Приймак, Микола (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
The main direction of research into periodic signals with a variable period is the construction of their Fourier series, which is equivalent to replacing the signals with their analytical functions, which are Fourier series, with further research not of the signals themselves, but of their series. The obtained results open up promising directions for the study of real signals with a variable period, in particular, electrocardiograms obtained during or after the action of a resting agent on the body.